Daphnia magna and Gammarus pulex, novel promising agents for biomedical and agricultural applications - Abdelrahman M. Khattab; Hamdy A. Abo-Taleb; Amer M. Abdelaziz; Mohamed A. M. El-Tabakh; Mohamed M. M. El-feky; Mohammed Abu-Elghait (Scientific Reports, 2022)
Abstract Various studies have shown the importance of using different types of Zooplankton biomasses as an additional substance in the diet of fish. In addition, the drainage water of the fish cultures could be used in plant irrigation. In this study, biomasses of water flea Daphnia magna and Gammarus pulex collected and tested, for the first time, their effect against pathogenic microorganisms and on plant germination. The results showed significant antibacterial activity of D. magna and G. pulex against Staphylococcus aureus and Pseudomonas aeruginosa bacteria, as well as antifungal activity against Alternaria solani and Penicillium expansum, which gives the possibility to be used as biocontrol against these bacteria and plant pathogenic fungi. Furthermore, both animals showed positive activity in the germination rate of Vicia faba seed, reaching 83.0 ± 3.5 and 86.0 ± 3.8%, respectively. In conclusion, the biomasses of D. magna and G. pulex are promising and effective agents for their use in the medical field against some pathogenic microbes and as stimulators of plant growth.